Sacrifice and the body [ biblical anthropology and Christian self-understanding - Dunnill, John (New critical thinking in religion, theology, and Biblical studies, 2013)
What is sacrifice? For many people today the word has negative overtones, suggesting loss, or death, or violence. But in religions, ancient and modern, the word is linked primarily to joyous feasting which puts people in touch with the deepest realities. John Dunnill's study brings together insights from social anthropology, biblical studies, liturgy and Trinitarian theology, exploring debates in sociology and cultural studies. Through a positive view of sacrifice, the author contributes to contemporary Christian debates on atonement and salvation